Soil Salinity Drives the Distribution Patterns and Ecological Functions of Fungi in Saline-Alkali Land in the Yellow River Delta, China - Yang, Chao; Sun, Juan (Frontiers in Microbiology, 2020)
High soil salinity is the main factor that limits soil microbial activity in the Yellow River Delta (YRD); however, its effects on fungal community and ecological function are unknown. Here, we comparatively investigated the diversity and structures of soil fungal communities targeting the internally transcribed fungal spacer gene using Illumina MiSeq sequencing methods under a salt gradient with five levels, namely, Low: low-salinity soil, Medium: medium-salinity soil, High: high-salinity soil, Extreme: extreme-salinity soil, and a non-salted site as the control (Non-saline). The results show that bulk density (BD) values significantly increased (p < 0.05), while significantly lower values of soil total carbon (TC), nitrogen (TN), and fungal Shannon and Chao indexes were observed as the salinization gradient increased (p < 0.05). The relatively high levels of the families Nectriaceae and Cladosporiaceae distinguished two of the clusters, indicating two enterotypes of low (Non-saline and Low) and high (Medium, High, and Extreme) salinity soils, respectively. The family Nectriaceae was most abundant in the networks, and the positive correlations were more pronounced than negative correlations; however, Cladosporiaceae was the family most negatively correlated with others based on the network analysis. At the ecological function level, plant saprotroph and litter saprotroph were significantly less abundant in extremely saline soil than non-saline soil. The change in soil properties (TC, TN, and BD) caused by soil salinization (salt and EC) regulated the diversity of soil fungal communities, and ecological function, as indicated by Pearson correlation analyses. We suggest further investigation into the ecological functions of soil microorganisms in the extremely saline-alkaline soils of the YRD.